CHARACTER EDUCATION AS A RESPONSE TO THE PHENOMENON OF BULLYING IN THE INDUSTRIAL ERA 4.0 FOR STUDENTS AT SMK TRIDHARMA GORONTALO STATE UNIVERSITY - Ngiu, Zulaecha; Al Hamid, Saleh; Sahi, Yayan (PT. Jurnal Center Indonesia Publisher, 2025)
Bullying among students is increasingly complex in the era of the Industrial Revolution 4.0, especially in the form of digital bullying that affects students' mental health and character. This service activity aims to provide character education in response to this phenomenon, so that students are able to build awareness and resilience in facing digital social pressure. The service methods used include interactive lectures, value simulation, and case study-based mentoring. This activity involved 34 students as the main target and 3 resource persons as facilitators The results of the activity showed an increase in participants' understanding of the form and impact of digital bullying, as well as the growth of concern and proactive attitude to create a safe school environment. Participants also showed improved ability to manage emotions, understand the importance of strong character, and not respond to pressure with aggressive actions. Based on these results, it is recommended that character education based on anti-bullying values continue to be strengthened through continuous habituation and training programs, in order to form a resilient and adaptive young generation in the digital era.